Ab initio study of structural, electronic, and thermal properties of Ir_{1-x}Rh_{x} alloys - Sh. Ahmed; M. Zafar; M. Shakil; M.A. Choudhary (Condensed Matter Physics, 2015)
The structural, electronic, mechanical and thermal properties of Ir_{1-x}Rh_{x} alloys was studied systematically using ab initio density functional theory at different concentration (x = 0.00, 0.25, 0.50, 0.75, 1.00). The Special Quasirandom Structure method was used to make the alloys with FCC structure with four atoms per unit cell. The ground state properties such as lattice constant and bulk modulus were calculated to find the equilibrium atomic position for stable alloys. The calculated ground state properties are in good agreement with the experimental and previously presented other theoretical data. The electronic band structure and density of states were calculated to study the electronic properties for these alloys at different concentration. The electronic properties substantiate metallic behavior of alloys. The first principle density functional perturbation theory as implemented in quasiharmonic approximation was used for the calculation of thermal properties. We have calculated the thermal properties such the Debye temperatures, vibration energy, entropy, constant-volume specific heat and internal energy. The ab initio linear-response method was used for phonon densities of states calculations.